The Effect of Linearity of Teaching Tasks on Teacher Performance at SMP/MTs Muhammadiyah - Ningrum, Endang Widiarti; Usman, Nurodin (Prosiding University Research Colloquium, 2021)
SMP/MTs Muhammadiyah is a private school that is not given much attention by the government and its sustainability is very dependent on the foundation. The number of non-civil servant teachers causes the division of teaching tasks to be often not linear with the teaching field. This research was conducted in nine SMP/MTs Muhammadiyah Wonosobodistrict. This research is important to do in order to determine the effect of linearity ofteaching tasks on the performance of SMP/MTs Muhammadiyah teachers. Data collectionwas carried out using a questionnaire via google form because it was carried out duringthe Covid-19 pandemic. The data obtained were statistically analyzed using regressionanalysis techniques using the SPSS 2020 program. The results showed that the correlationcoefficient R was 0.434. The coefficient is significant after being tested using the F-test,the F value is 9.530 with a significance level of 0.004. Because of the significance of 0.004<0.05, it can be hypothesized that there is a significant positive effect of linearity ofteaching assignments on teacher performance. The results of this study are expected to beused to see the teacher map at SMP/MTs Muhammadiyah Wonosobo so that improvementscan be made in a better direction.